High-pressure absorption study of CO2 in aqueous N-methyldiethanolamine (MDEA) and MDEA-piperazine (PZ)-1-butyl-3-methylimidazolium trifluoromethanesulfonate bmimOTf hybrid solvents - Khan, S.N. (Elsevier B.V., 2018)
In present study, high pressure CO2 absorption performance of aqueous N-methyldiethanolamine (MDEA) and its hybrid solvents with anhydrous perazine (PZ) and ionic liquid (IL) 1-butyl-3-methylimidazolium trifluoromethanesulfonate bmimOTf were investigated. The absorption performance of hybrid solvents were carried out to investigate CO2 loading capacity (mol of CO2/mol of solvent), and apparent absorption rate (CO2 capture efficiency, overall rate constant). The CO2 loading capacity of aqueous MDEA and its hybrid solvents were experimentally investigated for a wide range of compositions between pressure ranges of 2 to 50 bar and at three different temperatures (303.15, 313.15, and 333.15 K). Furthermore, apparent absorption rate performance of hybrid solvents were determined at 303.15 K temperature and 2 bar pressure. The effect of temperature, CO2 partial pressure, and ionic liquid (IL) concentrations on CO2 loading of aqueous IL-amines hybrid solvents were also investigated. The results indicated that CO2 loading of hybrid solvents were increased with increase in CO2 partial pressure and IL concentration (up to 10 wt%), further increased concentration of IL suppressed CO2 loading capacity. The CO2 loading capacity of hybrid solvents were also reduced with rise in system's temperature. The addition of IL and anhydrous PZ significantly enhanced CO2 capture efficiency (nCO2) and overall absorption rate constant (k) of aqueous MDEA solvent. Â© 2017 Elsevier B.V.